Nrf2 Is a Potential Modulator for Orchestrating Iron Homeostasis and Redox Balance in Cancer Cells - Zhang, Lingyan; Zhang, Jian; Jin, Yuanqing; Yao, Gang; Zhao, Hai; Qiao, Penghai; Wu, Shuguang (Frontiers in Cell and Developmental Biology, 2021)
Iron is an essential trace mineral element in almost all living cells and organisms. However, cellular iron metabolism pathways are disturbed in most cancer cell types. Cancer cells have a high demand of iron. To maintain a rapid growth and proliferation, cancer cells absorb large amounts of iron by altering expression of iron metabolism related proteins. However, iron can catalyze the production of reactive oxygen species (ROS) through Fenton reaction. Nuclear factor (erythroid‐derived 2)- like 2 (Nrf2) is an important player in the resistance of oxidative damage by inducing the transcription of antioxidant genes. Aberrant activation of Nrf2 is observed in most cancer cell types. It has been revealed that the over activation of Nrf2 promotes cell proliferation, suppresses cell apoptosis, enhances the self-renewal capability of cancer stem cells, and even increases the chemoresistance and radioresistance of cancer cells. Recently, several genes involving cellular iron homeostasis are identified under the control of Nrf2. Since cancer cells require amounts of iron and Nrf2 plays pivotal roles in oxidative defense and iron metabolism, it is highly probably that Nrf2 is a potential modulator orchestrating iron homeostasis and redox balance in cancer cells. In this hypothesis, we summarize the recent findings of the role of iron and Nrf2 in cancer cells and demonstrate how Nrf2 balances the oxidative stress induced by iron through regulating antioxidant enzymes and iron metabolism. This hypothesis provides new insights into the role of Nrf2 in cancer progression. Since ferroptosis is dependent on lipid peroxide and iron accumulation, Nrf2 inhibition may dramatically increase the sensitivity to ferroptosis. The combination of Nrf2 inhibitors with ferroptosis inducers may exert greater efficacy on cancer therapy.